STUDI TSUNAMI INUNDATION MODELLING PADA PANTAI TANJUNG SETIA LAMPUNG DENGAN PEMANFAATAN SOFTWARE DELFT3D - Mardika, M Gilang Indra; Mashuri, Mashuri; Dukhi Safaraz, Muhammad (Jurnal Infrastruktur, 2024)
Tanjung Setia Beach is located in the West Coast area of Lampung Province. This location is very vulnerable of disaster such as tsunami, because it is on the edge of a geologically active continent with a coastline facing the Indian Ocean and distinguished by the confluence of tectonic plates. With such conditions at any time a tsunami disaster can occur and cause damage to the area. One of the weaknesses in the Tanjung Setia coastal tourist area on, West Coast of Lampung Province, is non exist of hazard maps or KRB (Disaster Prone Vulnerability) maps made by the National Center for Volcanology and Disaster Mitigation. Modeling the propagation of tsunami waves by determining the distribution pattern of tsunami waves and implementing several planned wave height values and historical wave height is a basic step of disaster mitigation in the area. Using Delft3D 4.04.01 software based on data and scenario analysis can produce wave propagation in the area. The height and wave period of the plan are calculated using the hindcasting method and are based on the SPM 1984 standard and then used as input in Delft3D modeling software. From the calculation results, the height and wave period of the maximum plan for the 15 year is 3.01 m with a period of 8.21 s, the 25 year is 3.16 m with a period of 8.49 s and the 50 year is 3.37 m with a period of 8.87 s. In addition, historical tsunami wave heights of 3.6 m, 8 m and 15 m are also used as inputs in the Delft3D model. The results of propagation planned wave does not cause a significant tsunami disaster. As a result of wave propagation based on the historical height of tsunamis used, 3.6 m wave does not cause tsunami disasters in the area and take 35 minutes to reach coastal areas, while waves of 8 and 15 meters are able to cause tsunami disasters on land, which takes 27-34 minutes to reach the coast. All three scenarios qualify for model accuracy in shallow seas. From the results of mapping using GIS software, the maximum propagation of the scenario of high waves of 8 meters on land as far as 803 meters and waves of 15 meters as far as 872 m from the coastline.